Three-dimensional simulation of natural convection in cavities with side opening - Sezai, I; Mohamad, AA (Emerald Group Publishing Ltd, 1998)
Naturally buoyant flow and heat transfer in a cubic cavity with side opening is analyzed numerically. Vertical wall of the cavity is at a higher temperature than the ambient, while other walls are assumed to be adiabatic. Numerically accurate results are presented for Rayleigh numbers of 10(3) to 10(6) for a fluid having a Prandtl number of 0.71. Unstable flow is predicted for Ra = 1 x 10(7). The aim of the work is twofold; studying three-dimensional flow and heat transfer in a cavity and comparing three-dimensional results with two-dimensional approximation to verify the validity of the two-dimensional model. Convection fluxes are calculated using QUICK scheme with ULTRA-SHARP flux limiter for two and three-dimensional simulation. The results indicate that as Rayleigh number increases the difference between two and thr;ee dimensional predictions increases. Also, it is found that this difference is greater for the flow field than for the rate of heat transfer.
Keywords: heat transfer; natural convection; open cavities